2017
DOI: 10.1002/art.40123
|View full text |Cite
|
Sign up to set email alerts
|

The Therapeutic Efficacy of Botulinum Toxin in Treating Scleroderma‐Associated Raynaud's Phenomenon: A Randomized, Double‐Blind, Placebo‐Controlled Clinical Trial

Abstract: Objective To assess the therapeutic efficacy of local injections with Botulinum Toxin Type-A (Btx-A) in improving blood flow to the hands of patients with Raynaud's Phenomenon (RP) secondary to scleroderma. Methods In this randomized, double-blind, placebo-controlled clinical trial (ClinicalTrials.gov #NCT02165111), patients with scleroderma-associated RP received Btx-A (50 units in 2.5 mL) in one randomly selected hand and sterile saline (2.5 mL) in the opposite hand. Follow-up at 1 and 4 months post-inject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
140
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(146 citation statements)
references
References 35 publications
3
140
0
3
Order By: Relevance
“…One other study has investigated the effect of Btx-A injected via a dorsal approach [24]. Bello et al performed a randomised double-blind placebo controlled clinical trial in patients with scleroderma associate RP using Btx-A in one randomly selected hand and sterile saline in the opposite hand [24]. This study followed 40 patients for 1 and 4 months post injection using laser Doppler imaging, patient-reported outcomes and physical exam.…”
Section: Discussionmentioning
confidence: 99%
“…One other study has investigated the effect of Btx-A injected via a dorsal approach [24]. Bello et al performed a randomised double-blind placebo controlled clinical trial in patients with scleroderma associate RP using Btx-A in one randomly selected hand and sterile saline in the opposite hand [24]. This study followed 40 patients for 1 and 4 months post injection using laser Doppler imaging, patient-reported outcomes and physical exam.…”
Section: Discussionmentioning
confidence: 99%
“…9 However, a randomized, placebocontrolled, double-blind clinical trial conducted on 40 patients with SSc has shown that BTX-A did not significantly improve blood flow to the hands of patients with SSc-associated RP, but that patient-reported severity of RP showed a statistically significant improvement in hands treated using BTX-A. 12 In this randomized study, it was suggested that the negative results might have been due to the screening methods, which allowed for the inclusion of patients with large vessel disease, such as radial or ulnar artery occlusion. 12 In addition, BTX-A was injected into the web space on the dorsal surface of the hand to prevent hand weakness.…”
Section: Discussionmentioning
confidence: 99%
“…12 In this randomized study, it was suggested that the negative results might have been due to the screening methods, which allowed for the inclusion of patients with large vessel disease, such as radial or ulnar artery occlusion. 12 In addition, BTX-A was injected into the web space on the dorsal surface of the hand to prevent hand weakness. 12 A more distal injection site was used in this randomized study than that reported in some previous studies, including in our reports.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has shown promise as a therapeutic option for patients with severe RP in the fingers that is refractory to other treatments 2 3. However, overall evidence conflicting and further randomised controlled trials (RCTs) are needed if Btx-A is to become a viable treatment option 5. Furthermore, there are currently no studies in the literature that report the use of Btx-A for the treatment of RP in the toes.…”
Section: Introductionmentioning
confidence: 99%